Can Dexrazoxane and Carvedilol prevent Doxorubicin-induced nephrotoxicity? - Szponar Jaroslaw; Gorska Agnieszka; Ostrowska-Lesko Marta; Wielgomas Bartosz; Mandziuk Slawomir (Current Issues in Pharmacy and Medical Sciences)
Doxorubicin (DOX) is a cytostatic drug with a broad spectrum of anticancer activity that has been used in oncology for over 50 years. Among many adverse effects in humans, the most dangerous is late dilated cardiomyopathy, which appears even years after completion of therapy. However, in cats, the critical organ for the toxic effects of DOX is the kidney. Herein, nephrotoxicity is manifested as azotemia. The main aim of our study was to evaluate the protective effect of dexrazoxane (DEX) and carvedilol (CVD) against the nephrotoxic effects of DOX. Nephrotoxicity studies were performed in a rat model of repeated DOX administration. Analyzed blood morphological, biochemical and histopathological findings revealed that DEX has a dual effect: it positively impacts DOX-induced histological alterations and creatinine levels while negatively affecting urea concentration. Thus, the results do not support univocally recommend DEX to prevent nephrotoxicity caused by DOX in cats. However, further studies using initially lower doses of DEX are needed to assess the prevention of nephrotoxicity in cats clinically treated with DOX.